1996
DOI: 10.3109/00365529609003116
|View full text |Cite
|
Sign up to set email alerts
|

Secretor Status and Human Leucocyte Antigens in Coeliac Disease

Abstract: This study shows no firm relationship between the non-secretor state and coeliac disease, nor any difference in the distribution of HLA markers among secretor and non-secretor coeliacs. It is unlikely, therefore, that the secretor gene is the much sought-after second coeliac gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
2
3
0
Order By: Relevance
“…The prevalence of Le expression among patients with or without H. pylori infection was not signi¢cantly di¡erent from the prevalence of Le antigen expression (27%), as reported previously in a group of controls originating in the region from which our patient sample was drawn [17]. In our current sample of dyspeptic patients, non-secretors exhibited a combination of endoscopically visible antral gastritis, duodenitis, gastric ulcer or duodenal ulcer no more frequently than secretors.…”
Section: Discussionsupporting
confidence: 75%
“…The prevalence of Le expression among patients with or without H. pylori infection was not signi¢cantly di¡erent from the prevalence of Le antigen expression (27%), as reported previously in a group of controls originating in the region from which our patient sample was drawn [17]. In our current sample of dyspeptic patients, non-secretors exhibited a combination of endoscopically visible antral gastritis, duodenitis, gastric ulcer or duodenal ulcer no more frequently than secretors.…”
Section: Discussionsupporting
confidence: 75%
“…The prevalence of Le a expression among patients with or without H. pylori infection was not significantly different from the prevalence of Le a antigen expression (27%), as reported previously in a group of controls originating in the region from which our patient sample was drawn [17]. In our current sample of dyspeptic patients, non‐secretors exhibited a combination of endoscopically visible antral gastritis, duodenitis, gastric ulcer or duodenal ulcer no more frequently than secretors.…”
Section: Discussionsupporting
confidence: 76%
“…The association of non-secretor status with CelD was first suggested by Dickey et al (31). In a follow-up study by Heneghan et al (32), the non-secretor status did not associate significantly with CelD and the authors concluded that the 'secretor gene' was unlikely to be a CelD susceptibility gene.…”
Section: Discussionmentioning
confidence: 93%
“…The association of non‐secretor status with CelD was first suggested by Dickey et al . In a follow‐up study by Heneghan et al , the non‐secretor status did not associate significantly with CelD and the authors concluded that the ‘secretor gene’ was unlikely to be a CelD susceptibility gene. Recent studies have however shown that there is a relationship between the composition of gut microbiota and protection from or susceptibility to certain infections .…”
Section: Discussionmentioning
confidence: 94%